Behavioural effects of imprinted genes. (April 2015) - Davies, Jennifer R; Dent, Claire L; McNamara, Gráinne I; Isles, Anthony R
Highlights: Imprinted genes can influence behaviour via a number of mechanisms. Direct effects are illustrated by SNORD115 and MAGEL2, key genes underlying PWS. Imprinted genes regulate maternal supply and foetal demand of nutrients. Imbalance in nutrient supply caused by Igf2 leads to abnormal offspring behaviour. Imprinting genes may also be influenced by the pre-natal and post-natal environment. Abstract : The importance of imprinted gene effects on brain and behaviour is becoming increasingly clear. In addition to roles in neurodevelopmental disorders such as Prader–Willi and Angelman syndromes, changes in expression of imprinted genes contribute to neuropsychiatric illness more generally. Imprinted genes are also critical for placental function, and can influence adult behavioural outcomes via effects on the supply and demand of nutrients from the mother. Finally, the high level of epigenetic regulation and parental specific monoallelic expression make this subset of mammalian genes candidates for mediating the behavioural effects of exposure to an adverse pre-natal and/or post-natal environment. Here we provide an overview of recent developments in our understanding of the different mechanisms via which imprinted genes can influence behaviour.